Effects of Accreditation Program on Leadership, Organizational Culture, Activity and Performance of Hospital Management - sik Woo, Jung; hoon Kim, Young; sung Kim, Han; jung Kim, Hyo (International Journal of Engineering and Technology, 2018)
This study aimed to look into changes in patient safety of medical institutions and improvements in the quality of medical services with the implementation of the accreditation program and investigate the influences and relationships of the leadership, organizational culture and hospital management activity in accredited medical institutions with their management performance perceived by workers at the accredited hospitals. To summarize the results of the study, there were significant impacts of the accreditation program on the increase in the efficiency of the hospitals and the promotion of the spirits of employees. But referring to the finding that it did not have any significant influence relationship with the increase in their income of medical treatment or cost reduction. Political alternatives from financial perspective should be prepared in order to attract spontaneous participation in the accreditation of the medical institutions in the future.Â Â
Keywords: Accreditation Program; Leadership; Organizational Culture; Balanced Scorecard